Discussion on the Timing of Balloon Occlusion of the Abdominal Aorta during a Caesarean Section in Patients with Pernicious Placenta Previa Complicated with Placenta Accreta. (2nd November 2017) - Zhu, Baoju; Yang, Kaili; Cai, Lina
Abstract : Objective . This paper is aimed at investigating the role and value of the timing of balloon occlusion of the abdominal aorta during caesarean section in patients with pernicious placenta previa complicated with placenta accreta. Methods. 79 cases admitted to the Second Affiliated Hospital of Zhengzhou University from September 2015 to December 2016 were treated with ultrasound mediated abdominal aortic balloon occlusion. Among them, 42 cases, whose balloon occlusion time was selected before the delivery and transverse incision was taken, were group A. The other 37 cases were group B, whose timing of balloon occlusion was selected after the delivery and the uterine incision made trying to avoid the placenta or double incisions. The intraoperative blood loss, utilization of blood, and other indicators were compared between the two groups. Results. The intraoperative blood loss in groups A and B was 413.8 ± 105.9 ml and 810.3 ± 180.3 ml, and the utilization of blood products in groups A and B was 30.23% and 89.2%. The total hysterectomy rate was 2.53% (2/79), with no hysterectomies in groups A and 2 cases in group B. Conclusion. The balloon occlusion of the abdominal aorta before the delivery combined with a transverse incision is more effective.